2022
DOI: 10.1021/acsanm.2c02215
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Molybdate/Graphene Nanocomposite for Electrochemical Detection of Mercury

Abstract: We developed a flexible electrode based on a bismuth molybdate/graphene (BiM/GR) nanocomposite for electrochemical detection of mercury (Hg2+). The formation of the BiM/GR nanocomposite was systematically examined with suitable characterization studies. The BiM/GR-modified electrodes exhibit a high electrocatalytic performance toward Hg2+ detection comparable to other electrodes. The excellent electrocatalytic activity of the BiM/GR nanocomposite can be attributed to its good conductivity, synergistic effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The low Hg 2+ content poses a significant challenge to the sensitivity and detection limit of the electrochemical sensors. To enhance the performance of sensors, plenty of materials have been proposed as the sensing elements, such as graphene, , oligonucleotides, , metal–organic frameworks, , and other polymers. Fu et al reported a sensor of Zr­(IV)-based MOFs with specifically attached thioether side groups allowing Hg 2+ to be easily adsorbed and detected .…”
Section: Introductionmentioning
confidence: 99%
“…The low Hg 2+ content poses a significant challenge to the sensitivity and detection limit of the electrochemical sensors. To enhance the performance of sensors, plenty of materials have been proposed as the sensing elements, such as graphene, , oligonucleotides, , metal–organic frameworks, , and other polymers. Fu et al reported a sensor of Zr­(IV)-based MOFs with specifically attached thioether side groups allowing Hg 2+ to be easily adsorbed and detected .…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO requirement, the limit for Hg 2+ in drinking water is 6 µg/L, which poses a great challenge to the sensors [13]. To improve the performance of the electrochemical sensors, plenty of novel materials have been proposed and applied as the sensing elements, including metal-organic frameworks (MOFs) [14][15][16], graphene [17][18][19], carbon nanotubes [20][21][22], oligonucleotides [23][24][25], etc. For instance, Mariyappan et al reported the electrochemical detection of Hg 2+ using a nanocomposite of a Sr@FeNi-S nanoparticle and carbon nanotube with the limit of detection (LOD) of 0.1 µg/L and a wide linear range of 10 µg/L-55.8 mg/L [26].…”
Section: Introductionmentioning
confidence: 99%